2020
DOI: 10.1016/j.anbehav.2020.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of female song provides insight into the evolution of sex differences in a widely studied songbird

Abstract: Understanding the patterns and processes related to sexual dimorphism and sex differences in diverse animal taxa is a foundational research topic in ecology and evolution. Within the realm of animal communication, studies have traditionally focused on male signals, assuming that female choice and male-male competition have promoted sex differences via elaboration of male traits, but selection on females also has the potential to drive sexual differentiation in signals. Here, we describe female song in barn swa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 132 publications
0
3
0
Order By: Relevance
“…The two song types that female red-winged blackbirds sing are different in structure compared to male song (Beletsky, 1983; Catchpole and Slater, 2008), but there is no detail on what syllable types they may share. Some species have similar syllable structure between the sexes but have differences in the overall or particular spectral parameters of their song (Dutour and Ridley, 2020; Hahn et al, 2013; Wilkins et al, 2020; Yamaguchi, 1998). For example, northern cardinal ( Cardinalis cardinalis ) female song has been described as a neotenic version of male song, but it also differs from males in the amplitude of harmonics and syllable stereotypy (Yamaguchi, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The two song types that female red-winged blackbirds sing are different in structure compared to male song (Beletsky, 1983; Catchpole and Slater, 2008), but there is no detail on what syllable types they may share. Some species have similar syllable structure between the sexes but have differences in the overall or particular spectral parameters of their song (Dutour and Ridley, 2020; Hahn et al, 2013; Wilkins et al, 2020; Yamaguchi, 1998). For example, northern cardinal ( Cardinalis cardinalis ) female song has been described as a neotenic version of male song, but it also differs from males in the amplitude of harmonics and syllable stereotypy (Yamaguchi, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…4.2 Escuchándolas en Colombia.-Concretamente, en el Neotrópico el conocimiento sobre la prevalencia del canto en las hembras está pobremente documentado, a pesar de que se conoce que las hembras no sólo producen cantos facultativos, sino que también pueden realizar exhibiciones acústicas junto con los machos para formar duetos vocales (Logue & Gammon 2004, Hall 2009, Templeton et al 2013, Odom et al 2017, Hathcock & Benedict 2018. En la zona tropical, el canto de las hembras se ha descrito como menos complejo o frecuente que el de los machos (e.g., Hypocnemis peruviana e H. subflava; Tobias et al 2011; Hirundo rustica erythrogaster, Wilkins et al 2020), pero se destacan algunas investigaciones en especies tropicales en donde se describe que las hembras, i) cantan con más frecuencia que los machos, pero sus parámetros acústicos se superponen entre los sexos (e.g., Icterus pustulatus; Price et al 2008 Seeholzer & Gamarra 2020). Particularmente, en aquellas especies en donde machos y hembras lucen plumajes casi iguales, se ha llegado a asumir que todos los cantos son producidos por los machos, limitando el análisis de los patrones evolutivos en la variación vocal de las aves (Price et al 2008, Price 2015, Derryberry et al 2018.…”
Section: Fenología Vocal-el Estudio De Los Cantos De Las Aves Inicial...unclassified
“…Estas condiciones han resultado en que, por décadas, el estudio del comportamiento vocal en hembras se haya descuidado. Afortunadamente, esta tendencia está cambiando en los últimos años, demostrando que las hembras pueden exhibir comportamientos complejos asociados al uso de vocalizaciones (Ficken et al 2002, Riebel 2003, Wilkins et al 2020. A pesar de que las habilidades vocales de las hembras no han sido estudiadas ampliamente, sus preferencias por ciertos cantos o características acústicas específicas han recibido mayor atención, ya que estas preferencias tienen implicaciones evolutivas en el contexto de selección sexual y éxito reproductivo (Nowicki & Searcy 2004), por ejemplo, la preferencia por cantos locales versus cantos foráneos.…”
Section: Aprendizaje Vocal Y Neuroetología Del Cantounclassified
“…However, recent studies examining selection pressures in songbirds have suggested that greater variability in female songs may be selected for if female vocal signals are more limited in diversity and duration (Collins et al 2009, Wilkins et al 2020).…”
Section: Evolutionary Implicationsmentioning
confidence: 99%